The Elimination of Neglected Tropical Diseases: A Case Study Exemplifying How Foreign Assistance Funding Can Be Catalytic in Reducing the Burden of Major Global Health Conditions. (12th August 2019) - Wainwright, Emily; Evans, Darin; Rotondo, Lisa; Pou, Bolivar; Yevstigneyeva, Violetta; Zoerhoff, Kathryn L; Ottesen, Eric A; Reithinger, Richard
Abstract: In 2006, following direct advocacy and published rationale, the US Agency for International Development (USAID) established a neglected tropical diseases (NTDs) program to support the scale-up of integrated platforms to target the elimination and control of 5 NTDs—lymphatic filariasis, trachoma, onchocerciasis, schistosomiasis, and soil-transmitted helminthiasis. By 2017, more than 2.3 billion NTD treatments had been delivered to at-risk populations in 25 countries, leveraging $19 billion in donated drugs—approximately $26 dollars in donated medicine per $1 spent by USAID. As a result, most of the supported countries are on track to achieve their elimination goals (for lymphatic filariasis and trachoma) by 2020 or 2021 and their control goals soon thereafter. Though "small" when compared to other global health initiatives, this investment proved to be catalytic, and indeed highlights how foreign assistance funding can be transformative, in reducing the burden of major global health conditions such as NTDs. Abstract : Eliminating neglected tropical diseases became a 21st century possibility through advances in science and public health, but it became a reality only after bilateral foreign assistance funding provided implementation support in global collaborations with pharmaceutical companies, other donors, and the World Health Organization.